EIDINOW, Esther and KINDT, Julia (eds.). The Oxford Handbook of Ancient Greek Religion. Oxford and New York: Oxford University Press, 2015. p. xxii + 708. ISBN 9780199642038. - Roubekas, Nickolas P. (Classica - Revista Brasileira de Estudos Clássicos, 2016)
.